Peran Teori Keadulatan Tuhan pada Perang Kediri dan Tumapel pada Pembentukan Hukum di Indonesia - Sarip Sarip (Kosmik Hukum, 2020)
The sovereignty of God in the state administration of the Kingdom of Indonesia can be seen from the words of Ken Arok attacking the kingdom of Kediri, "O Pastors who adhere to Shiva and Buddhism. Please bless me to have the title Bhatara Guru ”. The study of God's sovereignty can be clearly seen from the history of Ken Arok, who was the king of Tumapel, who succeeded in using God's sovereignty to gain power over Kediri. So the question is the extent to which the existence of the struggle for God's sovereignty in Indonesia which underlies divine values. Ken Arok as the ruler of Tumapel who is a subordinate of Kediri has committed an offense of royal state order. What was done by Ken Arok in terms of International Law as "belligerent". Ken Arok's movement to gain power by committing offenses on the state administration of the kingdom, legalized by the laws of the royal state at that time, as well as international law today. In addition to evidence of the theory of God's sovereignty which was applied by Ken Arok to strengthen his power, in modern times too, the theory of God's sovereignty was practiced by Soekarno during the Old Order. As proof of the theory of God's Sovereignty during the Soekarno era came from the minister of religion of the Republic of Indonesia who at that time was held by Wahid Hasyim, who considered it important to build a magnificent mosque as gratitude for Indonesia's independence in the struggle against the invaders.Keywords: sovereignty, God, struggle, kingdom